Common institutional design, divergent results: A comparative case study of collaborative governance platforms for regional water planning. Issue 111 (September 2020) - Bell, Emily; Scott, Tyler A.
Highlights: Collaborative platforms leave a "paper trail" of documents to be analyzed. Topic modeling can trace patterns of deliberation in collaborative governance. A common collaborative platform design can beget widely different processes. Consultants play a key role in shaping collaborative governance processes and outputs Abstract: Environmental governance challenges often span geographic and sectoral boundaries, requiring collaboration between diverse stakeholders and multilateral decision making. To facilitate such efforts, policymakers and public managers create and support platforms that provide a structured framework for promoting collaborative governance. As the collaborative platform model is often centrally initiated – e.g., when state or national actors create a system of local collaborative resource management platforms – cross-case comparison is particularly important for understanding how a common design leads to variance in procedures and outputs in local contexts. Many collaborative platforms leave a "paper trail" of documents such as meeting records and plans. This analysis compares 10 identically designed and simultaneously initiated regional water planning platforms in the State of Georgia. Drawing on 106 meeting reports, we apply topic modeling to these meeting documents to generate replicable and scalable measures of how participant actions and interest representation unfold over time. Specifically, we measure topical focus on water planning issues over time, and compare these process-phase measures between councils and against the content of the resulting plan developed by each planning council. While existing literature has focused on how institutional design features such as representation and decision-rules shape procedural outcomes and outputs, we observe considerable variation in procedural behavior and plan outputs despite the fact that all 10 platforms share a common design. The consulting firm selected to direct each local platform is shown to be associated with both the topical focus of each regions' planning discussion and the BMPs selected in regional plans. This comports with recent evidence pointing to the important – and largely overlooked – role that technical consultants play in environmental governance and regulatory processes.